2023
DOI: 10.1111/trf.17232
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐specific IgG subclass composition in recipient mice can indicate the degree of red blood cell alloimmunization as well as discern between primary and secondary immunization

Abstract: Background: Despite the vast antigen disparity between donor and recipient red blood cells (RBCs), only 2%-6% of transfusion patients mount an alloantibody response. Recently, RBC antigen density has been proposed as one of the factors that can influence alloimmunization, however, there has been no characterization of the role of antigen density along with RBC dose in primary and secondary immunization. Study Design and Methods: To generate RBCs that express distinct antigen copy numbers, different quantities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Interestingly, the lowest antibody dose of 0.2 μg was able to cause a trend toward enhancement for the HEL med ‐RBCs (Figure 1B), which was not seen for the HEL hi ‐RBCs (Figure 1D). This could potentially be related to the magnitude of the HEL hi ‐RBC IgG response, which as described previously by our laboratory, was maximal 15 or might indicate that an even lower quantity of AMIS‐inducing antibody is needed to induce enhancement.…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…Interestingly, the lowest antibody dose of 0.2 μg was able to cause a trend toward enhancement for the HEL med ‐RBCs (Figure 1B), which was not seen for the HEL hi ‐RBCs (Figure 1D). This could potentially be related to the magnitude of the HEL hi ‐RBC IgG response, which as described previously by our laboratory, was maximal 15 or might indicate that an even lower quantity of AMIS‐inducing antibody is needed to induce enhancement.…”
Section: Resultssupporting
confidence: 59%
“…We previously reported that antigen copy number not only influences the magnitude of the recipient's immune response but can also alter the composition of the IgG response with the induction of all four IgG subclasses requiring a maximal primary immunogenic stimulus or secondary exposure for submaximal stimuli. 15 Here, we further characterized the IgG subclass response under AMIS conditions. Due to the predominance of the IgG1 subclass in the anti-HEL polyclonal antibody used (Table S1), we did not analyze the AMIS effect for this subclass.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations